2022
DOI: 10.3390/jcm12010077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Frailty Risk on Oral Intake and Length of Hospital Stay in Older Patients with Pneumonia: A Historical Cohort Study

Abstract: The aim of this study was to examine the association between frailty risk and outcomes in older patients with pneumonia. For this purpose, the JMDC multi-center database was used, and a historical cohort study was conducted to examine the association between the Hospital Frailty Risk Score (HFRS) and oral intake prognosis and length of hospital stay in older patients hospitalized with pneumonia. Patients were classified into low-risk (HFRS < 5), intermediate-risk (HFRS = 5–15), and high-risk (HFRS > 15) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…A similar trend was observed for hospital admissions for acute myocardial infarctions and heart failure 32 . More recently, a 2023 Japanese study also demonstrated the association of higher HFRS scores with higher rates of prolonged hospitalization (LOS > 15 days and LOS > 30 days) amongst 98 420 patients with pneumonia 33 . A local study of 902 patients admitted to a tertiary hospital also demonstrated that patients with delirium had higher HFRS scores and had greater 30‐day mortality (OR 2.52) and 30‐day readmission (OR 2.18) 21 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A similar trend was observed for hospital admissions for acute myocardial infarctions and heart failure 32 . More recently, a 2023 Japanese study also demonstrated the association of higher HFRS scores with higher rates of prolonged hospitalization (LOS > 15 days and LOS > 30 days) amongst 98 420 patients with pneumonia 33 . A local study of 902 patients admitted to a tertiary hospital also demonstrated that patients with delirium had higher HFRS scores and had greater 30‐day mortality (OR 2.52) and 30‐day readmission (OR 2.18) 21 .…”
Section: Discussionsupporting
confidence: 58%
“…32 More recently, a 2023 Japanese study also demonstrated the association of higher HFRS scores with higher rates of prolonged hospitalization (LOS > 15 days and LOS > 30 days) amongst 98 420 patients with pneumonia. 33 A local study of 902 patients admitted to a tertiary hospital also demonstrated that patients with delirium had higher HFRS scores and had greater 30-day mortality (OR 2.52) and 30-day readmission (OR 2.18). 21 Patients with delirium were also shown to have a higher prevalence of infections such as pneumonia (37.7% vs. 25.3%).…”
Section: Discussionmentioning
confidence: 97%
“…Nutrition has been well-studied in in-hospital patients with CAP for its relationship with frailty [ 30 ] and dysphagia [ 31 ] and as a risk factor for poor outcomes [ 32 ]. Nevertheless, little is known about nutritional status in older adults after CAP discharge except in relation to COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%